FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK IBU DALAM PEMBERIAN MAKANAN BAGI BALITA USIA 12-60 BULAN BERSTATUS GIZI KURANG DI WILAYAH PUSKESMAS LENGKONG KABUPATEN NGANJUK - Yolanda Purwana; Raden Widiatrilupi; Rosyidah Alfitri (Poltekkes Kemenkes Medan, 2024)
Nutritional status in children under five is closely related to various factors, including maternal age, maternal education, family income, maternal nutritional knowledge, maternal attitudes and maternal practices in providing food. This study aims to determine the factors that influence mothers' practices in providing food to toddlers aged 12-60 months with malnutrition status in the Lengkong Community Health Center area. Method The type of research is quantitative research, with a cross sectional study approach. The research sample was mothers who had toddlers aged 12-60 months with malnutrition, a total of 30 children taken using purposive sampling. Nutritional status data based on anthropometric measurements of BW/U is compared with the WHO_NCHS Z-score value. Data analysis was carried out using univariate analysis and bivariate analysis. The results of bivariate analysis showed mother's age (p= 0.713), mother's last education (p=0.015), family income (p=0.256). maternal nutritional knowledge (p-0333), and maternal attitude (p=0.006). Meanwhile, from the multivariate analysis, it was found that maternal education (p=0.216), maternal family income (p=0.462) and maternal attitude (p=0.998). Based on the results of the multivariate analysis, the mother's attitude factor is the factor that has the most influence on the malnutrition status of children under five because the value obtained is <0.998. The discussion of factors that influence mothers' practices in providing food for toddlers with low nutritional status is due to the characteristics of the mother, education and family income), knowledge and attitudes. In conclusion, it can be concluded that there are three factors that influence mothers' practices in providing food for toddlers aged 12-60 months with malnutrition status, namely maternal education, family income and maternal attitudes.